2023
DOI: 10.3390/agriculture13071287
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic and Fruit Colorimetric Analysis of Hungarian Sour Cherry Genebank Accessions

Abstract: Sour cherry is one of the most important horticultural crops in the Hungarian market. Its flavour combination makes it ideal for fresh consumption as well as canned products. The Hungarian and European markets have requested for new varieties to be introduced, making the evaluation of breeding and prebreeding material a crucial point. A total of 30 sour cherry accessions from the genebank collection were investigated for their potential inclusion into the breeding program. The main aim of the study was to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Despite identifying all the metabolites in the four cultivars, PCA analysis revealed that the difference in sour cherry metabolites was majorly due to the genotype differences. Our results for the metabolic information of dark-flesh cultivars ‘Heimann R’ and ‘Gorsemska’ are in correspondence with the results observed for Turkish sour cherry cultivars [ 23 ].…”
Section: Resultssupporting
confidence: 90%
“…Despite identifying all the metabolites in the four cultivars, PCA analysis revealed that the difference in sour cherry metabolites was majorly due to the genotype differences. Our results for the metabolic information of dark-flesh cultivars ‘Heimann R’ and ‘Gorsemska’ are in correspondence with the results observed for Turkish sour cherry cultivars [ 23 ].…”
Section: Resultssupporting
confidence: 90%
“…One approach involves screening collections for specific traits of interest, such as protein and lysine content in wheat [9]. Alternatively, evaluating accessions based on their breeding potential considers factors like color profiling and total polyphenolic content in sour cherry [10]. Optimization tools like Kullback-Leibler divergence assist in efficient resource allocation and selecting accessions for genotyping [11].…”
Section: Introductionmentioning
confidence: 99%